Gestión Administrativa para mejorar el Clima Laboral en el Centro de Prohibición de Libertad de Babahoyo - Espinoza Andaluz, Rommel Amador (2017)
The Municipal Jail was created in 1917, this center was built by the Cantonal Government of Babahoyo, since its inauguration it was called the Babahoyo Municipal Jail, after which it ceased to be municipal and was known as the Babahoyo Jail. At present, the National Directorate of Social Rehabilitation has granted it the title of Center for the Deprivation of Liberty of Adult Persons in conflicts with the Babahoyo Law, its main objective is the social and economic reintegration of persons deprived of liberty (PPL) of this public institution is located in Av. 9 of October between the streets Mejía between and Ricaurte